STUDI TENTANG PENGETAHUAN GIZI IBU DAN KEBIASAAN MAKAN PADA RUMAH TANGGA DI DAERAH DATARAN TINGGI DAN PANTAI - Ali Khomsan; Faisal Anwar; Dadang Sukandar; Hadi Riyadi; Eddy Setyo Mudjajanto (Food and Nutrition Society of Indonesia, 2006)
Eating habits refer to the behavior of a person or a group of people in satisfying the need for food, which involves attitude, beliefs, and choice of food. To understand eating habits, what ought to be considered are food consumption (quantity and quality), preference of certain food, beliefs, taboo, and attitude toward certain foods. This research aims to assess mother’s nutrition knowledge and food habits of the households. The study was conducted in a highland area of Bogor Regency and a coastal area of Indramayu Regency, West Java, Indonesia. In Bogor, 375 samples and in Indramayu 376 samples were selected randomly, so the total samples are 751. The data was collected through questionnaires. Mother’s nutrition knowledge is better in Indramayu than in Bogor. The eating frequency of 1-2 times daily is still dominant in the households of both locations of research. A food priority for the members (under five year old children) of households who are prone to nutritional problems is important to reduce the risk of malnutrition. The consumption of food from animal sources (meat and eggs) in both regions of research is generally still low, i.e. less than a piece of meat/week, and less than 1 egg/week, except for the consumption of fish in Indramayu, which is relatively high. The vegetable consumption in Bogor is relatively high, but fruit consumption is lower than that in Indramayu.